Empowering the Community’s Economy through Productive Zakat : A Comparative Study of Yusuf Al-Qardhawi’s and Sahal Mahfudh’s Thoughts - Khasanah, Maulida; Maulidya Perdana, Oggy (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
The reality of Muslims suffering from poverty is inversely proportional to the ideals of Islam which calls for poverty alleviation, especially through zakat. The ineffectiveness of zakat is due to the fact that its distribution is still consumptive, not productive. Therefore, this study aims to examine the thoughts of Yusuf al-Qardhawi and Sahal Mahfudh who pay serious attention to productive zakat as a medium for community economic empowerment. This research is classified as a normative and qualitative approach in the form of a literature study to examine data sources that contain the thoughts of Al-Qardhawi and Sahal. The main formulation is to compare al-Qardhawi and Sahal's thoughts on community economic empowerment through productive zakat in terms of background thought, main ideas, subjects, target objects, standard limits and operational steps. The results of this study have two findings. First, Al-Qardhawi proposes the idea of ​​community economic empowerment by improving zakat management, good subjects, distribution with Priority Fiqh principles, theoretical-idealist operational steps. Second, Sahal proposes the idea of ​​community economic empowerment aimed at community economic problems and improving zakat management, good subjects, zakat distribution in accordance with the provisions of Islamic jurisprudence, and practical theoretical implementation steps